Pengaruh Ekonomi Makro SBI, EXR, M2, GDP dan OIL terhadap Inflasi di Indonesia Tahun 2020–2024 - Lukminarti, Elita; Nurdin, Novi Puspa; Nova, Monica; Rizqi, Adinda (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2025)
This study aims to analyze the influence of macroeconomic variables on inflation in Indonesia during the 2020–2024 period, encompassing the COVID-19 pandemic and the subsequent economic recovery. The independent variables examined include Bank Indonesia’s benchmark interest rate (SBI), the exchange rate of the rupiah against the US dollar (EXR), money supply (M2), real Gross Domestic Product (GDP), and global oil prices (OIL), with inflation as the dependent variable. A quantitative approach using multiple linear regression was applied to quarterly data spanning five years (20 observations). The results indicate that SBI has a significant negative effect on inflation, while EXR, M2, and OIL have significant positive effects. GDP shows a positive but statistically insignificant effect. The model's adjusted R² is 70.9%, suggesting that most of the variation in inflation can be explained by these variables. These findings align with macroeconomic theory and provide valuable recommendations for monetary and fiscal policies to maintain price stability in Indonesia. Keywords: Inflation, interest rate, exchange rate, money supply, oil price, macroeconomy.